INTRUSION DETECTION SYSTEM FOR ZIGBEE-BASED IOT USING DATA ANALYSIS RULES - Fal Sadikin; Nuruddin Wiranda (Jurnal Teknologi Informasi Universitas Lambung Mangkurat (JTIULM), 2023)
The market for Internet of Things (IoT) products and services has grown rapidly. It has been predicted that the deployment of these IoT applications will grow exponentially in the near future. However, the rapid growth of IoT brings new security risks and potentially opens new types of attacks for systems and networks. This article outlines various techniques for detecting known attacks in ZigBee-based IoT systems. We introduced an Detection System (IDS) specific for ZigBee using data analytics method, that are used to provide an accurate detection method for known attacks. This article looks at our IDS implementation covering a wide variety of detection techniques to detect known attacks ZigBee IoT systems.